Vampire knight. Vol. 11 - Hino, Matsuri (Shojo beat manga., 2010)
The Night Class at Cross Academy has been abolished. Zero still attends the Day Class while carrying out his duties as a vampire hunter. Yuki now lives hidden away at the Kuran residence with Kaname, but can she embrace the life of a pureblood vampire?